The Impact of Putting Preventive Measures in Place for Children Who Have Received Breast Milk in the Past - Dian Eka Nursyam; Zaliha Binti Harum; Syamimi Samah; Irwadi (CV. Get Press Indonesia, 2025)
Stunting is one of the most common causes of death in children with a history of breastfeeding. This study aimed to investigate the effectiveness of stunting prevention efforts in children History of Breastfeeding. The systematic literature review (SLR) method was used to collect and analyse research findings related to risk factors, intervention effectiveness, and best practices. The SLR was conducted in the PubMed, ProQuest, Scopus, ScienceDirect, and Google Scholar databases from 2019 to 2023. Ten articles met all inclusion criteria and were analysed in depth. A combination of exclusive breastfeeding, maternal nutrition education, growth monitoring, complementary feeding, supplementation for pregnant women, and community empowerment approaches has been proven to be most effective in reducing stunting. There was a significant difference in pregnant women's efforts to prevent stunting before and after receiving information, and the average previous score increased to 72 after receiving the information. The findings of this study confirm that the effective of stunted prevention programmes is greatly influenced by the availability of adequate inputs (funding, human resources, anthropometric equipment) and optimal implementation processes (monitoring, education, cross-sector coordination).